2008
DOI: 10.1021/ic8001477
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Soft and Hard X-Ray Absorption Spectroscopy to Characterize Metallodrug/Protein Interactions: the Binding of [trans-RuCl4(Im)(dimethylsulfoxide)][ImH] (Im = imidazole) to Bovine Serum Albumin

Abstract: The reaction of bovine serum albumin (BSA) with [ trans-RuCl 4(Im)(dimethylsulfoxide)][ImH] (Im = imidazole) (NAMI-A), an experimental ruthenium(III) anticancer drug, and the formation of the respective NAMI-A/BSA adduct were investigated by X-ray absorption spectroscopy (XAS) at the sulfur and chlorine K-edges and at the ruthenium K- and L 3-edges. Ruthenium K and L 3-edge spectra proved unambiguously that the ruthenium center remains in the oxidation state +3 after protein binding. Comparative analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 37 publications
(79 reference statements)
3
40
1
3
Order By: Relevance
“…However, ruthenium K and L 3 -edge spectra unambiguously verified that the ruthenium center remained in the oxidation state of +3 upon protein binding. Sulfur K-edge spectra remained the same during the binding, whereas chlorine K-edge spectra indicated changes in the chlorine chemical environment during the NAMI-A binding to albumin, attributed to the release of two chlorides [30] and the subsequent replacement by two water molecules [34].…”
Section: Speciation Analysis Of Metallometabolites By X-ray Absorptiomentioning
confidence: 95%
See 1 more Smart Citation
“…However, ruthenium K and L 3 -edge spectra unambiguously verified that the ruthenium center remained in the oxidation state of +3 upon protein binding. Sulfur K-edge spectra remained the same during the binding, whereas chlorine K-edge spectra indicated changes in the chlorine chemical environment during the NAMI-A binding to albumin, attributed to the release of two chlorides [30] and the subsequent replacement by two water molecules [34].…”
Section: Speciation Analysis Of Metallometabolites By X-ray Absorptiomentioning
confidence: 95%
“…Trans-RuCl 4 (Im)(DMSF)(ImH) (NAMI-A; Im = imidazole; DMSF = dimethylsulfoxide) entered clinical trials in the year of 2000 as an antimetastatic agent, whereas trans-RuCl 4 (In) 2 (InH) (In = indazole) (KP1019) entered in 2003 as an agent against colon carcinomas. Ascone and coworkers reported an XANES investigation of the binding environment of bovine serum albumin to NAMI-A [30]. The relative binding affinities of NAMI-A to human serum albumin and other biomolecules (such as DNA) confirmed the preferential interaction of NAMI-A to proteins over nucleotides [31].…”
Section: Speciation Analysis Of Metallometabolites By X-ray Absorptiomentioning
confidence: 99%
“…Emerging drugs (in phase I clinical trials) such as the potential Ru(III) chorido-indazole anti cancer drug (KP1019) and the anti-metastatic agent, NAMI-A, [87][88] have been analysed in cell culture media, blood serum and cultured mammalian cells to understand the transformations that occur to the metal centre. Lay and coworkers [89] isolated Ru(III)-BSA complexes by gel-filtration chromatography, freeze-dried the product and analysed it by XAS.…”
Section: Anti-inflammatory Agentsmentioning
confidence: 99%
“…The interactions of metallodrugs with macromolecular blood components have been recognized as crucial for their biodistribution and efficacy. 17-21 In particular, ruthenium complexes of known anticancer activity have been shown to interact with human serum albumin (HSA), 20,22,23 and with apotransferrin (ATf). 24,25 We have shown that such protein-drug interactions also take place with ruthenium-chloroquine complexes with antimalarial activity.…”
Section: Introductionmentioning
confidence: 99%